Dietitian assistant opportunities within the nutrition care process for patients with or at risk of malnutrition: a systematic review. Issue 1 (8th January 2021) - Rushton, Alita; Edwards, Anna; Bauer, Judith; Bell, Jack J.
Abstract: Aim: Shifting to models of care that incorporate delegation of nutrition care process actions to dietitian assistants could facilitate effective and efficient nutrition care delivery. This review aimed to determine if delegation of malnutrition care activities to dietitian assistants, when compared with routine nutrition care practices influences patient, healthcare and/or workforce outcomes for adult hospital inpatients with or at risk of malnutrition. Methods: This review was undertaken in accordance with PRISMA guidelines, with five databases (CINAHL, Medline, PsycINFO, Embase and Scopus) searched systematically for studies published up to and including February 2020. Exclusion criteria included review articles and studies conducted in community settings. Results: The search yielded 3431 results, with 11 studies eligible for inclusion. Across all domains of the nutrition care process, there is emerging evidence dietitian assistants may improve the delivery of nutrition care practices, patient, healthcare and workforce outcomes. Findings demonstrated various roles and scope of dietitian assistants' practice throughout the studies. Positive patient outcomes were found when dietitian assistants were part of a multi‐disciplinary model of care. Conclusions: Implementing delegation of components of the nutrition care process to dietitian assistants is vital in the current health climate and should be considered in a future multidisciplinary model of nutrition care. Exploration of dietitian assistant roles and opportunities are required to expand and strengthen the evidence.